Skip Row, Furrow Irrigation Optimizes Peanut Pod Yield, Net Returns, and Irrigation Water Use Efficiency. Issue 1 (11th April 2019) - Leininger, S.D.; Krutz, L.J.; Sarver, J.M.; Gore, J.; Henn, A.; Bryant, C.J.; Atwill, R.L.; Spencer, G.D.
Abstract : Core Ideas: Land preparation method, planting flat or on a raised bed, has no effect on peanut pod yield. In furrow‐irrigated environments, should peanut be irrigated on every furrow or every other furrow? Irrigating every other furrow, in furrow‐irrigated peanut, increased irrigation water use efficiency. Soil water potential in the rooting zone of furrow‐irrigated peanut ( Arachis hypogea L.) may be influenced through seed bed formation and irrigation strategy. The objective of this study was to determine if bed formation and irrigation strategy improves peanut pod yield and profitability in rainfed and furrow‐irrigated environments. The effects of land preparation method (flat vs. bed) and irrigation strategy (every furrow, every other furrow, and rainfed) on peanut pod yield, net returns above tillage and irrigation costs, and irrigation water use efficiency were investigated near Stoneville, MS on a Bosket very fine sandy loam (fine‐loamy, mixed, active, thermic Mollic Hapludalfs). Relative to the rainfed environment, irrigation either had no effect or improved yield 1.8‐fold regardless of land preparation method and irrigation strategy. Pooled over land preparation method, irrigating every other furrow either had no effect or improved net returns above irrigation costs up to $238/acre. Independent of year and land preparation method, irrigating every other furrow increased irrigation water use efficiency 5.3‐fold relative to irrigating every furrow. Our data indicate that yield, net returns above irrigation costs, and irrigation water use efficiency are most often optimized for peanut in the Mid‐Southern USA by irrigating every other furrow regardless of bed formation.